Special issue law firms, legal culture, and legal practice - Sarat, Austin (Bingley, U.K. : Emerald, 2010)
Large law firms have become a dominant feature of the legal landscape in the United States and elsewhere. This volume of Studies in Law, Politics, and Society examines the situation of large law firms. The articles collected here address the following questions: How has the large law firm altered, or adapted to, the ideals/ideology of the legal profession? How do law firms function as organizations? What happens to firms when they globalize their practices? What is the situation of scholarship on large law firms? Has the firm been incorporated into boarder interdisciplinary configurations? What, if any,new paradigms ofstudy of firms areon the horizon?.
Measuring law firm culture / Elizabeth Chambliss -- Rejecting the culture of independence : corporate lawyers as committed to their clients / Robert Eli Rosen -- Law firm strategies for human capital : past, present, future -- William D. Henderson -- Taxes and death : the rise and demise of an American law firm / Milton C. Regan -- From policy to practice : assessing the effect of large law firm pro bono structure on pro bono commitment / Steven A. Boutcher -- If you become his second wife, you are a fool : shifting paradigms of the roles, perceptions, and working conditions of legal secretaries in large law firms / Felice Batlan -- Racial and ethnic minority representation in large U.S. law firms / Elizabeth H. Gorman, Fiona M. Kay.
Keywords: Law -- Trial Practice; Law -- General; Law & society; Courts & procedure; Law offices; Law firms; Sociological jurisprudence